Adjudication as a resolver in mitigating construction payment issues: A literature review / Syarifah Nur Nazihah Syed Jamalulil ... [et al.] - Syed Jamalulil, Syarifah Nur Nazihah; Ab.Wahid, Abdul Muhaimin; Lop, Nor Suzila; Shuib, Mohammad Nasharudine; Mat Salleh, Norazlin (2021)
Construction industry has been a core contributor to the Malaysian economy. However, payment issues have remained controversial since they affect the entire delivery chain of the construction industry. This has caused difficulties in managing payments as it involves many parties with large amounts of money. To mitigate payment issues, Construction Industry Development Board (CIDB) with collaboration of Master Builder Association Malaysia (MBAM) and other stakeholders in the construction industry had proposed Adjudication as a resolver through the introduction of Construction Industry Payment and Adjudication Act 2012 (CIPAA). Therefore, the aim of this research is to address the practicality of Adjudication as resolver in the construction payment issues. Despite its practicality, it is relevant to investigate the current performance of adjudication through CIPAA 2012 in the Malaysian construction industry to determine its effectiveness. Therefore, current issues on performance of adjudication executed through CIPAA 2012 have been reviewed. This research posits that it is essential to highlight the practicality of Adjudication as resolver in payment issues for better improvement of construction industry cash flow in the future.